A kind of water-based highly dispersed titanium dioxide and preparation method thereof
By forming a silicon phosphate envelope layer on the surface of the titanium dioxide substrate of titanium dioxide and optionally adding an alumina envelope layer, the problem of unsatisfactory dispersion effect in aqueous systems is solved, and its application performance in aqueous coatings and inks is significantly improved.
Patent Information
- Application Number
- CN202211101387.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The dispersion effect of existing titanium dioxide in aqueous systems is not ideal, affecting the hiding power and glossiness, and it is difficult to effectively apply in water-based coatings and inks.
By forming a silicon phosphate envelope layer on the surface of the titanium dioxide substrate and optionally adding an aluminum oxide envelope layer, the dispersion and corrosion resistance of the titanium dioxide are improved.
It significantly improves the dispersion and corrosion resistance of titanium dioxide in water-based coatings and inks, and enhances its application performance in water-based systems.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium dioxide preparation, and particularly relates to a water-based highly dispersed titanium dioxide and a preparation method thereof. Background Art
[0002] As people pay more and more attention to the environment, the application of titanium dioxide in water-based systems is highly favored. However, the dispersion effect of general-purpose titanium dioxide in water-based systems is not ideal, which directly affects the application performance of the system formula, such as hiding power and glossiness. If the water-based dispersibility of titanium dioxide is improved, it will not only promote the promotion of hydrophilic titanium dioxide in coatings, but also improve the application of water-based inks. In addition, the application performance of water-based systems will also be effectively improved. Summary of the invention
[0003] The purpose of the present invention is to provide a water-based highly dispersed titanium dioxide and a preparation method in order to solve the deficiencies of the prior art.
[0004] The purpose of the present invention is achieved by the following technical solutions:
[0005] A water-based highly dispersed titanium dioxide comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer at least comprises a silicon phosphate coating layer.
[0006] Preferably, the silicon phosphate coating layer is prepared by the following steps:
[0007] First, add soluble silicate to the titanium dioxide-based material slurry with a slurry concentration greater than 400g / L, and then add phosphoric acid with a mass fraction greater than 85% until the pH of the slurry is adjusted to 2.8-3.2, and then add phosphoric acid with a mass fraction greater than 85% to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C.
[0008] Preferably, the amount of the soluble silicate added is 1 to 2% of the total mass of the titanium dioxide substrate in the slurry, calculated as SiO2;
[0009] After adjusting the pH, the amount of phosphoric acid added is calculated as P2O5, which accounts for 0.5-3% of the total mass of the titanium dioxide substrate in the slurry.
[0010] Preferably, the coating layer further includes an aluminum oxide coating layer located outside the silicon phosphate coating layer.
[0011] The method for preparing water-based highly dispersed titanium dioxide as described by Sang at least comprises the following steps:
[0012] First, a titanium dioxide-based material slurry is prepared, and then a soluble silicate and phosphoric acid are added to react to cause silicon phosphate to precipitate and deposit on the surface of the titanium dioxide substrate to form a silicon phosphate coating layer.
[0013] Preferably, the concentration of the titanium dioxide-based material slurry is 400-500 g / L in terms of TiO2, the soluble silicate is first added to the titanium dioxide-based material slurry, and then the phosphoric acid with a mass fraction greater than 85% is added to the titanium dioxide-based material slurry until the pH of the slurry is adjusted to 2.8-3.2, and finally a certain amount of phosphoric acid with a mass fraction greater than 85% is added to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C.
[0014] Preferably, the soluble silicate is added in the form of a solution, and the concentration of the solution is 300-350 g / L in terms of SiO2.
[0015] Preferably, the hydrothermal reaction is first reacted at 130-170° C. for 20-40 min, then reacted at 180-220° C. for 20-40 min, and finally reacted at 280-320° C. for 40-80 min.
[0016] Preferably, after the silicon phosphate coating, the slurry concentration is adjusted to 300-350 g / L, and then the alumina coating is carried out at 50-60°C.
[0017] Preferably, after the coating is completed, a step of adding a modifier is also included; the modifier is one or more combinations selected from silane coupling agents, fatty acids and derivatives, and surfactants, and the added amount accounts for 0.1-2% of the total mass of the titanium dioxide substrate in the slurry.
[0018] Preferably, after the treatment with the modifier, the method further comprises adjusting the pH of the slurry to 6.5 to 7.0.
[0019] Preferably, the preparation method further comprises:
[0020] S1. Prepare the titanium dioxide-based material slurry, adjust the slurry concentration to 400-500 g / L, then add the soluble silicate solution having a concentration of 300-350 g / L in terms of SiO2, add for 8-12 min, and homogenize for 4-6 min after addition;
[0021] S2. Then add the phosphoric acid with a mass fraction greater than 85%, adjust the pH of the slurry to 2.8 to 3.2, add for 20 to 40 minutes, and homogenize for 8 to 12 minutes after addition;
[0022] S3. Adjust the slurry temperature to 85-90°C;
[0023] S4. Continue to add the phosphoric acid having a mass fraction greater than 85% for 20 to 40 min;
[0024] S5. Then react at 130-170°C for 20-40 min, then react at 180-220°C for 20-40 min, and finally react at 280-320°C for 40-80 min;
[0025] S6. Adjust the slurry concentration to 300-350 g / L and the temperature to 50-60 ° C;
[0026] S7. Add a soluble aluminum salt solution for 20 to 40 minutes, and then homogenize for 20 to 40 minutes; the amount of the soluble aluminum salt added is calculated as Al2O3, and the amount added accounts for 1.5 to 3% of the total mass of the titanium dioxide substrate in the slurry;
[0027] S8. Add modifier and homogenize for 40 to 80 minutes;
[0028] S9. Adjust the pH of the slurry to 6.5-7.0 for 20-40 min, and then homogenize for 40-80 min;
[0029] S10. Then, the titanium dioxide product is obtained through water washing, flash evaporation and steam powdering.
[0030] The titanium dioxide with a silicon phosphate coating layer provided by the present invention has good dispersibility and corrosion resistance, and can be well applied to water-based paint or ink systems. DETAILED DESCRIPTION
[0031] The water-based highly dispersed titanium dioxide provided in the present application comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, and the coating layer comprises at least a silicon phosphate coating layer.
[0032] The present application coats the titanium dioxide surface with a silicon phosphate film layer, and the obtained titanium dioxide is applied to a water-based paint system, which can not only accelerate the drying speed of the water-based paint system, but also has rust resistance, and improves the corrosion resistance of titanium dioxide in the water-based paint system. Moreover, the coated silicon phosphate can increase the absolute value of the surface potential of the particles, increase the steric hindrance between the particles, and thus improve the dispersibility of titanium dioxide in the water-based paint system. In the prior art, the conventional dense silicon film layer is mainly used to improve the weather resistance of titanium dioxide, the loose silicon film layer mainly improves the hiding power, and the film layers such as aluminum phosphate and calcium phosphate are mainly used to improve the light resistance, and have no obvious effect on the dispersibility of titanium dioxide in the water-based system.
[0033] Therefore, the titanium dioxide with a silicon phosphate coating layer provided by the present invention has good dispersibility and corrosion resistance, and can be well applied to water-based coatings or ink systems.
[0034] Preferably, the silicon phosphate coating layer is prepared by the following steps:
[0035] First, add soluble silicate to a titanium dioxide-based material slurry with a slurry concentration greater than 400g / L, then add concentrated phosphoric acid with a mass fraction greater than 85% until the pH of the slurry is adjusted to 2.8-3.2, and then add concentrated phosphoric acid with a mass fraction greater than 85% to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C.
[0036] Under conventional titanium dioxide coating conditions (slurry concentration is generally 200-350g / L), dilute phosphoric acid (mass fraction is generally <50%) is added, and silicates such as sodium silicate will precipitate silicate in the process of adjusting from alkaline to acidic. Therefore, in order to avoid the precipitation of silicate, the present application adjusts the concentration of the titanium dioxide-based material slurry to ≥400g / L and uses concentrated phosphoric acid with a mass fraction of ≥85%. At this concentration, concentrated phosphoric acid has fewer ionized hydrogen ions, and adding concentrated slurry will not lead to the generation of a large amount of ionized hydrogen ions, thereby effectively preventing the precipitation of silicate. Finally, silicon phosphate precipitates under high temperature hydrothermal conditions and is evenly deposited on the surface of titanium dioxide.
[0037] Preferably, the amount of silicate added is calculated as SiO2, and the amount added accounts for 1-2% of the total mass of the titanium dioxide substrate in the slurry; the amount of phosphoric acid added after pH adjustment is calculated as P2O5, and the amount added accounts for 0.5-3% of the total mass of the titanium dioxide substrate in the slurry.
[0038] Preferably, the coating layer further includes an aluminum oxide coating layer located outside the silicon phosphate coating layer. The aluminum oxide coating layer can further improve the dispersibility of titanium dioxide.
[0039] The present invention also provides a method for preparing the above-mentioned water-based highly dispersed titanium dioxide, which comprises at least the following steps:
[0040] First, a titanium dioxide-based material slurry is prepared, and then a soluble silicate and phosphoric acid are added to react to cause silicon phosphate to precipitate and deposit on the surface of the titanium dioxide substrate to form a silicon phosphate coating layer.
[0041] Preferably, the titanium dioxide-based material slurry is chloride-process titanium dioxide slurry or sulfate-process titanium dioxide slurry.
[0042] Preferably, the concentration of the titanium dioxide-based material slurry is 400-500 g / L in terms of TiO2. A soluble silicate is first added to the titanium dioxide-based material slurry, and then phosphoric acid with a mass fraction greater than 85% is added to the titanium dioxide-based material slurry. It is further preferred that the mass fraction of phosphoric acid is 85-95%, until the pH of the slurry is adjusted to 2.8-3.2. Finally, a certain amount of phosphoric acid with a mass fraction greater than 85% is added to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C.
[0043] Preferably, the soluble silicate is added in the form of a solution, and the concentration of the solution is 300-350 g / L in terms of SiO2. In this range, the concentration of the soluble silicate solution is also relatively high, which can also prevent the generation of a large number of ionized hydrogen ions.
[0044] Preferably, the hydrothermal reaction is first reacted at 130-170° C. for 20-40 minutes, then at 180-220° C. for 20-40 minutes, and finally at 280-320° C. for 40-80 minutes. The three-stage heat preservation reaction can control the growth of silicon phosphate particles to be more stable, and make the deposited particles more complete in crystal form, and can also avoid hard agglomeration of particles caused by long-term high-temperature reaction.
[0045] Preferably, after silicon phosphate coating, the slurry concentration is adjusted to 300-350 g / L, and then aluminum oxide coating is performed at 50-60° C. Silicon phosphate coating can prevent silicic acid precipitation under concentrated slurry conditions, but when coating aluminum oxide, high concentrations easily lead to high slurry viscosity, which is not conducive to aluminum coating. Therefore, diluting the slurry concentration is beneficial to aluminum coating.
[0046] Preferably, after the coating is completed, a step of adding a modifier is included; the modifier is one or more combinations selected from silane coupling agents, fatty acids and derivatives, and surfactants, and the amount added accounts for 0.1-2% of the total mass of the titanium dioxide substrate in the slurry. The modifier treatment is performed after coating so that the titanium dioxide particles have both steric hindrance and double electric layer in the aqueous system, further improving the dispersibility.
[0047] Preferably, after the modifier treatment, the step of adjusting the pH of the slurry to 6.5-7.0 is also included. Under this pH condition, the water washing in the next stage can be effectively carried out and the pH of the titanium dioxide product can be maintained near neutral.
[0048] The present invention provides an embodiment of a preferred preparation method, which specifically comprises the following steps:
[0049] S1. Prepare a titanium dioxide-based material slurry, adjust the slurry concentration to 400-500 g / L, then add a soluble silicate solution having a concentration of 300-350 g / L in terms of SiO2, add for 8-12 min, and homogenize for 4-6 min;
[0050] S2. Then add phosphoric acid with a mass fraction greater than 85%, adjust the pH of the slurry to 2.8-3.2, add for 20-40 minutes, and homogenize for 8-12 minutes;
[0051] S3. Adjust the slurry temperature to 85-90°C;
[0052] S4. Continue to add a phosphoric acid solution having a mass fraction greater than 85% for 20 to 40 minutes;
[0053] S5. Then react at 130-170°C for 20-40 min, then react at 180-220°C for 20-40 min, and finally react at 280-320°C for 40-80 min;
[0054] S6. Adjust the slurry concentration to 300-350 g / L and the temperature to 50-60 ° C;
[0055] S7. Add a soluble aluminum salt solution for 20 to 40 minutes, and then homogenize for 20 to 40 minutes; the amount of aluminum salt added is calculated as Al2O3, and the amount added accounts for 1.5 to 3% of the total mass of the titanium dioxide substrate in the slurry;
[0056] S8. Add modifier and homogenize for 40 to 80 minutes;
[0057] S9. Adjust the pH of the slurry to 6.5-7.0 for 20-40 min, and then homogenize for 40-80 min;
[0058] S10. Then, the titanium dioxide product is obtained by washing, flash evaporation and steam powder. The soluble silicate is preferably sodium silicate, and the concentration of the sodium silicate solution is 300-350 g / L in terms of SiO2.
[0059] The processes not limited in the present invention, such as water washing, flash evaporation, steam powder, etc., are all carried out in conventional ways in the art.
[0060] Example 1
[0061] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 500g / L. Stirring is started, and 1% sodium silicate solution is added to the slurry. The concentration of the sodium silicate solution is 320g / L in terms of SiO2. The addition time is 10min and the homogenization time is 5min. The pH of the slurry is adjusted to 3.0 with 90% phosphoric acid by mass fraction. The addition time is 30min and the homogenization time is 10min. The temperature is raised to 90°C. A 1.8% phosphoric acid solution (in terms of P2O5) is added to the slurry. The mass fraction of the phosphoric acid solution is 2.5%. The slurry is 90% and the adding time is 30min; the slurry is transferred to a high temperature and high pressure reactor, and the temperature is programmed to react at 150℃ for 30min, 200℃ for 30min, and 300℃ for 1h; water is added to dilute the slurry to 350g / L, and the temperature is 55℃; 3.0% sodium aluminate solution is added to the slurry for 30min and homogenized for 30min; 0.15% silane coupling agent is added to the slurry and homogenized for 60min; pH is adjusted to 6.5 with dilute acid for 30min and homogenized for 60min. The product is obtained by water washing, flash evaporation and steam powder.
[0062] Example 2
[0063] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 400g / L. Stirring is started, and 1.5% sodium silicate solution is added to the slurry. The concentration of the sodium silicate solution is 350g / L in terms of SiO2. The addition time is 10min and the homogenization time is 5min. The pH of the slurry is adjusted to 3.0 with 90% phosphoric acid by mass fraction. The addition time is 30min and the homogenization time is 10min. The temperature is raised to 85°C. A 2.0% phosphoric acid solution (in terms of P2O5) is added to the slurry. The concentration of the phosphoric acid solution is 2.0%. The concentration is 90%, and the adding time is 30min; the slurry is transferred to a high temperature and high pressure reactor, and the temperature is programmed to react at 150℃ for 30min, 200℃ for 30min, and 300℃ for 1h; water is added to dilute the slurry to 350g / L, and the temperature is 50℃; 2.0% sodium aluminate solution is added to the slurry, and the adding time is 30min, and the homogenization is 30min; 0.1% silane coupling agent is added to the slurry, and the homogenization is 60min; the pH is adjusted to 7.0 with dilute acid, and the adjustment is 30min, and the homogenization is 60min. The product is obtained by water washing, flash evaporation, and steam powder.
[0064] Example 3
[0065] After the uncoated sulfuric acid titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 500g / L. Stirring is started, and 2% sodium silicate solution is added to the slurry. The concentration of the sodium silicate solution is 300g / L in terms of SiO2. The addition time is 10min and the homogenization time is 5min. The pH of the slurry is adjusted to 3.2 with 85% phosphoric acid by mass fraction. The addition time is 30min and the homogenization time is 10min. The temperature is raised to 90°C. 3.0% phosphoric acid (in terms of P2O5) solution is added to the slurry. The concentration of the phosphoric acid solution is 2.5g / L. The slurry is 85% and the adding time is 30min; the slurry is transferred to a high temperature and high pressure reactor, and the temperature is raised programmatically, and the reaction is carried out at 150℃ for 30min, 200℃ for 30min, and 300℃ for 1h; water is added to dilute the slurry to 300g / L, and the temperature is 50℃; 3.0% sodium aluminate solution is added to the slurry, and the adding time is 30min, and the homogenization is 30min; 0.2% silane coupling agent is added to the slurry, and the homogenization is 60min; the pH is adjusted to 6.5 with dilute acid, and the adjustment is 30min, and the homogenization is 60min. The product is obtained by water washing, flash evaporation, and steam powder.
[0066] Example 4
[0067] After the uncoated sulfuric acid titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 400g / L. Stirring is started, 1% sodium silicate solution is added to the slurry for 10 minutes and homogenized for 5 minutes; phosphoric acid is used to adjust the pH of the slurry to 2.8 for 30 minutes and homogenized for 10 minutes; the temperature is raised to 85°C; 1.0% phosphoric acid (in terms of P2O5) solution is added to the slurry for 30 minutes; the slurry is converted into Put it into a high-temperature and high-pressure reactor, program the temperature, react at 150℃ for 30min, 200℃ for 30min, and 300℃ for 1h; add water to dilute the slurry to 300g / L, the temperature is 50℃; add 2.0% sodium aluminate solution to the slurry, add time is 30min, homogenize for 30min; add 0.15% silane coupling agent to the slurry, homogenize for 60min; adjust the pH to 7 with dilute acid, adjust for 30min, and homogenize for 60min. Wash with water, flash evaporation, and steam powder to obtain the product.
[0068] Example 5
[0069] After the uncoated sulfuric acid titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 500g / L. Stirring is started, and 2% sodium silicate solution is added to the slurry. The concentration of the sodium silicate solution is 300g / L in terms of SiO2. The addition time is 10min and the homogenization time is 5min. The pH of the slurry is adjusted to 3.2 with 85% phosphoric acid by mass fraction. The addition time is 30min and the homogenization time is 10min. The temperature is raised to 90°C. 3.0% phosphoric acid (in terms of P2O 5) solution, the concentration of phosphoric acid solution is 85%, and the addition time is 30min; the slurry is transferred to a high-temperature and high-pressure reactor, and the temperature is programmed to react at 150℃ for 30min, 200℃ for 30min, and 300℃ for 1h; water is added to dilute the slurry to 300g / L, and the temperature is 50℃; 3.0% sodium aluminate solution is added to the slurry, and the addition time is 30min, and homogenization is 30min; dilute acid is used to adjust the pH to 6.5, adjust for 30min, and homogenize for 60min. Wash with water, flash evaporation, and steam powder to obtain the product.
[0070] Comparative Example 1 (Silicon-aluminum coating)
[0071] The uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted to a slurry concentration of 300 g / L. Stirring is started and the temperature is raised to 55°C. The pH of the slurry is adjusted to 10-10.5 with NaOH within 10 minutes. 3% Na2SiO3 is added within 40 minutes, the concentration of the Na2SiO3 solution is 150 g / L, and the homogenization time is 15 minutes. The pH is adjusted to 6.8 with H2SO4 within 120 minutes, and the homogenization time is 30 minutes. At the same time, 1.8% NaAlO2 solution and 1.2% Al2SO4 solution are added in parallel, the pH is maintained at 10-10.5, the addition time is 40 minutes, and the homogenization time is 20 minutes. The pH is adjusted to 5.8-6.2 with dilute H2SO4, the adjustment time is 30 minutes, and the homogenization time is 120 minutes. The product is obtained by water washing, flash evaporation, and steam powder.
[0072] Comparative Example 2
[0073] Foreign standard sample S.
[0074] The samples prepared in the examples and comparative examples were subjected to evaluation experiments on water dispersion (Table 1), water-based latex paint (Table 2) and water-based ink (Table 3), and the experimental results were as follows:
[0075] Table 1
[0076] Water dispersion Example 1 99.4% Example 2 99.1% Example 3 98.9% Example 4 99.3% Example 5 91.8% Comparative Example 1 62.7% Comparative Example 2 67.9%
[0077] Table 2
[0078] L b Covering power 60° gloss Example 1 96.85 1.55 94.80 78.2 Example 2 96.93 1.43 94.69 77.6 Example 3 96.29 1.94 94.77 74.0 Example 4 96.17 1.84 94.71 75.1 Example 5 96.39 1.87 94.36 70.2 Comparative Example 1 96.78 1.51 94.20 63.7 Comparative Example 2 96.49 1.71 94.04 67.9
[0079] Table 3
[0080] L b Covering power 20° gloss Example 1 94.99 1.61 72.72 74.9 Example 2 94.87 1.59 72.88 74.3 Example 3 94.24 1.84 72.86 71.1 Example 4 94.31 1.91 72.91 73.4 Example 5 94.27 1.92 72.08 70.3 Comparative Example 1 94.68 1.55 69.72 66.6 Comparative Example 2 94.39 1.87 69.83 67.9
[0081] It can be seen from the above table that the invention is significantly superior to the comparative example in terms of water dispersion, hiding power and glossiness.
[0082] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A water-based highly dispersed titanium dioxide, characterized in that: It comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer at least comprises a silicon phosphate coating layer; The silicon phosphate coating layer is prepared by the following steps: First, a soluble silicate is added to a titanium dioxide-based material slurry with a slurry concentration greater than 400 g / L, and then phosphoric acid with a mass fraction greater than 85% is added until the pH of the slurry is adjusted to 2.8-3.2, and then phosphoric acid with a mass fraction greater than 85% is added to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C; The hydrothermal reaction is firstly carried out at 130-170° C. for 20-40 min, then at 180-220° C. for 20-40 min, and finally at 280-320° C. for 40-80 min.
2. The water-based highly dispersed titanium dioxide according to claim 1, characterized in that: The amount of the soluble silicate added is 1-2% of the total mass of the titanium dioxide substrate in the slurry, calculated as SiO2; After adjusting the pH, the amount of phosphoric acid added is calculated as P2O5, which accounts for 0.5-3% of the total mass of the titanium dioxide substrate in the slurry.
3. The water-based highly dispersed titanium dioxide according to claim 1, characterized in that: The coating layer also includes an aluminum oxide coating layer located outside the silicon phosphate coating layer.
4. The method for preparing an aqueous highly dispersed titanium dioxide according to any one of claims 1 to 3, characterized in that: At least the following steps are included: First, a titanium dioxide-based material slurry is prepared, and then a soluble silicate and phosphoric acid are added to react so that silicon phosphate is precipitated and deposited on the surface of the titanium dioxide substrate to form a silicon phosphate coating layer; The silicon phosphate coating layer is prepared by the following steps: First, a soluble silicate is added to a titanium dioxide-based material slurry with a slurry concentration greater than 400 g / L, and then phosphoric acid with a mass fraction greater than 85% is added until the pH of the slurry is adjusted to 2.8-3.2, and then phosphoric acid with a mass fraction greater than 85% is added to form a silicon phosphate coating layer under a high temperature hydrothermal reaction at 130-320°C; The hydrothermal reaction is firstly carried out at 130-170° C. for 20-40 min, then at 180-220° C. for 20-40 min, and finally at 280-320° C. for 40-80 min.
5. The method for preparing water-based highly dispersed titanium dioxide according to claim 4, characterized in that: The concentration of the titanium dioxide-based material slurry is 400-500 g / L in terms of TiO2.
6. The method for preparing water-based highly dispersed titanium dioxide according to claim 5, characterized in that: The soluble silicate is added in the form of a solution, and the concentration of the solution is 300-350 g / L in terms of SiO2.
7. The method for preparing water-based highly dispersed titanium dioxide according to claim 4, characterized in that: After the silicon phosphate coating, the slurry concentration is adjusted to 300-350 g / L, and then the aluminum oxide coating is carried out at 50-60° C.
8. The method for preparing water-based highly dispersed titanium dioxide according to claim 4, characterized in that: After the coating is completed, the method further includes adding a modifier for treatment; the modifier is one or more combinations selected from silane coupling agents, fatty acids and derivatives, and surfactants, and the added amount accounts for 0.1-2% of the total mass of the titanium dioxide substrate in the slurry.
9. The method for preparing water-based highly dispersed titanium dioxide according to claim 8, characterized in that: After the modifier treatment, the method further includes adjusting the pH of the slurry to 6.5-7.
0.
10. The method for preparing an aqueous highly dispersed titanium dioxide according to any one of claims 4 to 9, characterized in that: The preparation method further comprises: S1. Prepare the titanium dioxide-based material slurry, adjust the slurry concentration to 400~500g / L, then add the soluble silicate solution with a concentration of 300~350g / L in terms of SiO2, add for 8~12min, and homogenize for 4~6min after addition; S2. Then add the phosphoric acid with a mass fraction greater than 85%, adjust the pH of the slurry to 2.8~3.2, add for 20~40min, and homogenize for 8~12min after addition; S3. Adjust the slurry temperature to 85~90℃; S4. Continue to add the phosphoric acid having a mass fraction greater than 85% for 20 to 40 min; S5. Then react at 130-170°C for 20-40 min, then react at 180-220°C for 20-40 min, and finally react at 280-320°C for 40-80 min; S6. Adjust the slurry concentration to 300~350g / L and the temperature to 50~60℃; S7. Add a soluble aluminum salt solution for 20 to 40 minutes, and then homogenize for 20 to 40 minutes; the amount of the soluble aluminum salt added is calculated as Al2O3, and the amount added accounts for 1.5 to 3% of the total mass of the titanium dioxide substrate in the slurry; S8. Add modifier and homogenize for 40-80 minutes; S9. Adjust the pH of the slurry to 6.5-7.0 for 20-40 minutes, and then homogenize for 40-80 minutes; S10. Then, the titanium dioxide product is obtained through water washing, flash evaporation and steam powdering.
Citation Information
Patent Citations
Preparation method of special titanium dioxide powder for high-gloss outdoor paint
CN110003687A